2022
DOI: 10.3390/agronomy12020503
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on the Agriculture Sector: Survey Analysis of Farmer Responses from Kerala and Tamil Nadu States in India

Abstract: The global COVID-19 pandemic has hit the agriculture sector hard around the world. A study was conducted to assess the impact of the pandemic on cropping patterns, crop management, usage of chemical inputs and their organic alternatives, harvesting, and marketing avenues through a survey approach in the two states of Kerala and Tamil Nadu in India. A total of 250 farmers participated in the study, the data was analyzed by Chi-square test and Kruskal–Wallis test. The assessment of the impact of COVID-19 on some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The maximum shortage among the pesticides was found to be 52% for insecticides, whereas 25% shortage was seen for herbicides. 26 The insufficiency of fertilizers and pesticides has an adverse impact on agrarian output. The encountered challenges necessitate pertinent actions to enhance the overall agro-food supply chain for sustainable development.…”
Section: Effect Of the Pandemic On The Agro-food Sector And Environmentmentioning
confidence: 99%
“…The maximum shortage among the pesticides was found to be 52% for insecticides, whereas 25% shortage was seen for herbicides. 26 The insufficiency of fertilizers and pesticides has an adverse impact on agrarian output. The encountered challenges necessitate pertinent actions to enhance the overall agro-food supply chain for sustainable development.…”
Section: Effect Of the Pandemic On The Agro-food Sector And Environmentmentioning
confidence: 99%
“…As an impact of COVID-19, just like other sector, agriculture sector was also hit and the financial situation of farmers remained precarious. A study conducted by Habanyati et al, (2022) reported that as part of COVID-19 lockdown farmers in Kerala were faced a lot of difficulties such as farm labor shortages, input shortages, machinery shortages, poor access to credit as well as consultancy and movement restrictions and this affected the financial condition of farmers. As a result, most of them were hesitant to implement new programmes or technology unless they received financial assistance from the government.…”
Section: Component Wise Extent Of Adoption In Ifs Unitsmentioning
confidence: 99%
“…Additionally, the mental and physical toll of the pandemic on farmers has also shaped the perception of their resilience and strength. The lockdown in India had an impact on agriculture sector, resulting in unharvested crops, labour shortages, and delays in planting the crops (Habanyati et al 2022) [5] . Farmers have had to adapt to new safety protocols, navigate uncertainties, and manage increased workloads.…”
Section: Introductionmentioning
confidence: 99%